Higher Education in Sylhet Division of Bangladesh: Performance of Private Universities - Md. Jahangir Alam (EDUCATIO: Journal of Education, 2024)
Higher education in Bangladesh has its roots in the British colonial period, and since the country's liberation in 1971, the government has placed significant emphasis on developing the education sector. This study aims to identify the structure, acts, laws, and commissions governing higher education in Bangladesh, with a particular focus on the Sylhet division. The study also assesses the performance of private universities within this division. Secondary data were gathered from various articles, websites, and relevant documents, while specific information regarding Leading University was obtained from the office of the Controller of Examinations. Descriptive statistics were employed to analyze the data. The findings indicate that the higher education sector in Bangladesh has undergone significant transformation, particularly following the implementation of the Private University Act of 1992. Among the 158 universities nationwide, only 10 are located in the Sylhet division, and among the 114 medical colleges, only 7 are situated in this region. Within Sylhet's four districts, the Sylhet district houses the majority of higher education institutions, while the Moulvibazar district has the fewest. The private universities in the Sylhet division have shown strong performance in terms of infrastructure, physical facilities, and teacher-student ratios, with Leading University identified as the top performer. However, this study primarily focuses on the opportunities available in higher education in the Sylhet division, and does not assess the quality of education. Future research could explore this aspect further.